Knowledge of Hand Hygiene Practices among Healthcare workers in Neonatal and Paediatric Intensive Care Unit of a tertiary care hospital of Odisha - Choudhury, Jasashree; Mahapatra, Anuspandana (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Background:The objective of this study was to assess the knowledge of hand hygiene of healthcare workers in the neonatal and paediatric intensive care unit in a tertiary care hospital. Methods : Study was conducted to assess the knowledge of hand hygiene for the five moments of hand hygiene of WHO. Healthcare workers were given a questionnaire during routine patient care on random basis and the data was collected. Data analysis was performed using SPSS software version 13. Results : A total of 50 health care workers were questioned during the observation period. Answers differed by role: nurses (25) and doctors (10).15 nurses have no knowledge of moments of hand hygiene and were excluded from study. Nurses were more likely to use soap and water compared to waterless-alcohol-based hand hygiene practices. Doctors were most likely to use alcoholic hand rub. Conclusion : Though knowledge of hand hygiene practice is high ,use of alcohol-based disinfectant was found to be very low compared to soap and water. Keywords: Hand hygiene, Health care, Soap and water, Alcohol hand rub.